Neighbourhood trajectories in Stockholm: Investigating the role of mobility and in situ change. (January 2023) - Vogiazides, Louisa; Mondani, Hernan
Abstract: This paper studies the dynamics of neighbourhood change and neighbourhood stability, using the case of Stockholm during the period 1990–2015. We employ Swedish register data and a three-step methodology to investigate to what extent and how neighbourhoods' characteristics change over time and the factors driving those changes. Firstly, we apply k-means clustering to a set of socioeconomic, housing and demographic characteristics at the neighbourhood level, and identify a typology of neighbourhood states. Secondly, we build neighbourhood trajectories out of the states over time and use sequence analysis to obtain ideal-typical neighbourhood trajectories. Finally, we decompose the neighbourhood change into selective mobility, i.e., the differences in the characteristics of in- and out-movers, and in situ change of sitting residents. Our results reveal a mixed picture, with the role of selective mobility and in situ change varying depending on the type of neighbourhood transition and the variable under consideration. Trajectories of neighbourhood upgrading towards elite status in the Stockholm city-centre and downward trajectories ending in vulnerability in the periphery are mainly driven by selective mobility. Other typical trajectories comprise the emergence of newly built elite areas and the ageing of certain middle-class areas, the latter mostly driven by ageing of sitting residents. Highlights: Stockholm's neighbourhoods have experienced gentrification and filtering. There is spatial diffusion of neighbourhoods' elite status and vulnerability. Neighbourhoods' profile tends to be stable over time. Neighbourhoods change by a complex interplay of mobility and in situ change.